Magnetic and radio-labeled bio-hybrid scaffolds to promote and track in vivo the progress of bone regeneration. (19th October 2021) - Campodoni, Elisabetta; Velez, Marisela; Fragogeorgi, Eirini; Morales, Irene; de la Presa, Patricia; Stanicki, Dimitri; Dozio, Samuele M.; Xanthopoulos, Stavros; Bouziotis, Penelope; Dermisiadou, Eleftheria; Rouchota, Maritina; Loudos, George; et al.
Abstract : This work describes the preparation, characterization and functionalization with magnetic nanoparticles of a bone tissue-mimetic scaffold composed of collagen and hydroxyapatite obtained through a biomineralization process. Abstract : This work describes the preparation, characterization and functionalization with magnetic nanoparticles of a bone tissue-mimetic scaffold composed of collagen and hydroxyapatite obtained through a biomineralization process. Bone remodeling takes place over several weeks and the possibility to follow it in vivo in a quick and reliable way is still an outstanding issue. Therefore, this work aims to produce an implantable material that can be followed in vivo during bone regeneration by using the existing non-invasive imaging techniques (MRI). To this aim, suitably designed biocompatible SPIONs were linked to the hybrid scaffold using two different strategies, one involving naked SPIONs (nMNPs) and the other using coated and activated SPIONs (MNPs) exposing carboxylic acid functions allowing a covalent attachment between MNPs and collagen molecules. Physico-chemical characterization was carried out to investigate the morphology, crystallinity and stability of the functionalized materials followed by MRI analyses and evaluation of a radiotracer uptake ([ 99m Tc]Tc-MDP). Cell proliferation assays in vitro were carried out to check the cytotoxicity and demonstrated no side effects due to the SPIONs. The achieved results demonstrated that the naked and coated SPIONs are more homogeneously distributed in the scaffold when incorporated during the synthesis process. This work demonstrated a suitable approach to develop a biomaterial for bone regeneration that allows the monitoring of the healing progress even for long-term follow-up studies.